2023
DOI: 10.1186/s12912-022-01161-0
|View full text |Cite
|
Sign up to set email alerts
|

What is nursing professionalism? a concept analysis

Abstract: Background Nursing professionalism plays an important role in clinical nursing. However, a clear conceptual understanding of nursing professionalism is lacking. Method Walker and Avant’s strategy was used to analyse the concept of nursing professionalism. We searched electronic databases, including PubMed, Scopus, and CINAHL, for studies published from 1965 to 2021. Quantitative or qualitative studies published in English that focused on nursing pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
34
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 85 publications
1
34
0
3
Order By: Relevance
“…Despite the perceived excessive workload, nurses reported no reduced quality of care and did not refer to care left incomplete or undone, a frequent problem for COVID_19 patients [39]. In fact, some reported that they developed greater closeness and communication with the patient because of the absence of family members demonstrating high levels of professionalism [40,41]. However, Hargreaves and colleagues (2022) emphasized nurses' concern about not being able to provide the same quality of care as before the pandemic [7].…”
Section: Discussionmentioning
confidence: 99%
“…Despite the perceived excessive workload, nurses reported no reduced quality of care and did not refer to care left incomplete or undone, a frequent problem for COVID_19 patients [39]. In fact, some reported that they developed greater closeness and communication with the patient because of the absence of family members demonstrating high levels of professionalism [40,41]. However, Hargreaves and colleagues (2022) emphasized nurses' concern about not being able to provide the same quality of care as before the pandemic [7].…”
Section: Discussionmentioning
confidence: 99%
“…Herein lies the danger of stereotyping, in which an element is assumed to confer value (at a cultural or social level) on the action regardless of the professional purpose it actually serves. A professional action, on the other hand, should produce effects that make possible the result that social or cultural value justifies as corresponding to the disciplinary perspective (Cao et al, 2023). For example, the idea of self‐care corresponds to a social value that enables the nurse to choose nursing interventions that empower the patient to care for himself (Matarese et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…1 A mix of educational formats is included by way of achieving professional satisfaction. 2 This can be a good learning experience because the presenter must prepare to speak to a new audience, follow guidelines for s ubmitting an abstract, and may discover new information from interacting with the audience. 3 One can become well-known in a specialty or as an expert on a specific topic if one presents that subject frequently.…”
Section: Skills Workhopmentioning
confidence: 99%
“…Presenting at conferences can support one' s career advancement and contribute to the development of other nurses as well as the dissemination of research, best practices, and innovations-ultimately improving patient care and the nursing profession. 1,2 Nurses who have completed the foundational stage of their careers and feel confident in their roles may want to share their knowledge with colleagues. Some who have continued their education and completed advanced degrees may be eager to present their research.…”
mentioning
confidence: 99%
See 1 more Smart Citation